2013
DOI: 10.1002/cbin.10070
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide protects endothelium from cadmium mediated leakiness

Abstract: Cadmium targets the vascular endothelium causing endothelial dysfunction and leakiness of endothelial barrier. Nitric oxide plays a major role in mediating endothelial functions including angiogenesis, migration and permeability. The present study investigates the nitric oxide effects on cadmium induced endothelial leakiness. Results of ex vivo and in vitro permeability assays showed that even a sub-lethal dose of cadmium chloride (1 µM) was sufficient to induce leakiness of endothelial cells. Cadmium drastica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 53 publications
(88 reference statements)
3
15
0
1
Order By: Relevance
“…Results also demonstrated that sFRP4 decreased NO production in EC irrespective of cell origin (micro-vs. macro-vascular EC) and that this inhibition remained effective up to 24 h post treatment. Our data parallels previous studies that have similarly shown altered endothelial actin cytoskeleton and increased vascular permeability following inhibition of NO synthesis [26,27,35].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Results also demonstrated that sFRP4 decreased NO production in EC irrespective of cell origin (micro-vs. macro-vascular EC) and that this inhibition remained effective up to 24 h post treatment. Our data parallels previous studies that have similarly shown altered endothelial actin cytoskeleton and increased vascular permeability following inhibition of NO synthesis [26,27,35].…”
Section: Discussionsupporting
confidence: 92%
“…DAF-FM was performed on EAhy926 cells treated with sFRP4 (250 pg/ml), Bradykinin (BK; 5 μM), SP (10 μM), 8-Br (50 μM), CAT (30 U), MnTBAP (10 μM) and their combinations with sFRP4 for 4 h as per the protocol described elsewhere [26]. L-Arg was used as positive control.…”
Section: Daf-fm Fluorimetric Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The HUVECs were then incubated with EHNs (5 μg mL −1 ), catalase (1200 units per mL) and MnTBAP (10 μM) for 4 h. Subsequently the media were replaced with 5 µM DAF-FM and incubated in the dark for 30 min at room temperature. The DAF-FM solution from each of the treatments was transferred to a 96 well microtitre plate and the fluorescence was measured using a fluorescence spectrophotometer 22,23 with λ ex : 495 nm and λ em : 515 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Increasing reports have reviewed the importance of the integrity of endothelial structure for viable vascular function (Kolluru et al 2006;Messner et al 2009;Knoflach et al 2011;Oliveira et al 2011). Additionally, there is a growing volume of evidence implicating the endothelium as a primary target of Cd toxicity (Prozialeck et al 2008;Nagarajan et al 2013). The components of the medial layer of the aorta-the smooth muscle cell (SMC) and connective tissue like elastin and collagen-contribute to the elasticity of the aorta (Shirwany and Zou 2010).…”
Section: Discussionmentioning
confidence: 99%